Blind signature scheme based on entangled quantum - Jian-wu LIANG; Xiao-hui WANG; Ying GUO; Zi CHENG (Tongxin xuebao)
Based on the principle of quantum entanglement swapping, a blind signature scheme based on quantum entanglement was proposed.Through being entangled and exchanged, particles prepared before could transform into entangled state. The measurements of new entangled particles complete signature and verification and realize the quantum communication, blind signature and verification. Different from the classical blind signatures which based on the mathematics difficulty, the scheme could guarantee not only the anonymity but also the unconditionally security.